Pengaruh Pemberian Pupuk Organik Granul terhadap Pertumbuhan dan Hasil Tanaman Padi (Oryza sativa L.) Varietas Ciherang pada Lahan Rawa Lebak - Ahmad Riyadi (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2012)
Rice is a food that produces rice. This food is a staple food for most Indonesians. Even as a staple food, rice can be replaced or substituted by other food ingredients, but rice has its own value for people who are accustomed to eating rice and cannot be easily replaced by other food ingredients. This study aims (i) to know the effect, and (ii) to get the best dose of granule organic fertilizer on the growth and yield of rice plants of Ciherang Varieties on lebak lowland. This research was conducted in Harusan Village, Amuntai Tengah District, North Hulu Regency, from February to May 2011. This study used a single randomized block design (RBD). The factors studied were 5 levels of granule organic fertilizer, namely: g0: 0 ton.ha-1, g1: 1 ton.ha-1 equivalent to or 8.571 g per clump or 0.3 kg per plot. g2: 2 ton.ha-1 is equivalent to 17.142 g per clump, or 0.6 kg per plot. g3: 3 ton.ha-1 is equivalent to 25,714 g per clump, or 0.9 kg per plot. g4: 4 ton.ha-1 is equivalent to 34.285 g per clump, or 1.2 kg per plot. The factors studied were as much as granule organic fertilizer. The results showed that the treatment of granular organic fertilizer dosage did not affect plant height, many tillers, but the treatment had a significant effect on the number of filled grain per clump. The treatment of granulated organic fertilizer dosage of 2 tons.ha-1 is equivalent to 17.142 g per clump, which is the best dose of the number of filled grain per clump